The Impact of Early Sports Specialisation on Injury Risk in Young Athletes: A Systematic Review - Afriani, Desi; Tomoliyus; Sukamti, Endang Rini; Alim, Abdul; Hermanto; Widiawati, Prisca (Indonesian Journal of Sport Management, 2025)
Background: Early sports specialization is often driven by the pursuit of achieving elite performance levels at younger ages. However, growing concerns have emerged regarding the potential negative consequences of this specialization, particularly the increased risk of injuries and the potential for psychological burnout among young athletes. Purpose: The primary purpose of this study is to systematically review the current body of literature to assess the impact of early sports specialization on the risk of injury in young athletes. Method: A systematic literature search was conducted utilizing the Sage and PubMed databases to identify relevant studies published between 2019 and 2025.  To maintain a focus on youth athletes in competitive or elite settings, studies that centered on recreational athletes were excluded from the analysis. Result: Early sports specialization is associated with a higher risk of injury among young athletes. This increased risk particularly applies to overuse injuries, such as stress fractures, tendinopathies, and joint issues, and psychological burnout. Conversely, athletes who engaged in multiple sports throughout their developmental years demonstrated a significantly lower risk of injury and reported higher levels of enjoyment and motivation in their chosen sports. Implications and Recommendation: Importance of re-evaluating current practices in youth athletic development programs. Sports organizations, coaches, and parents should exercise caution in promoting early specialization among young athletes and instead support a more balanced approach to youth training. Delaying specialization until after puberty and encouraging participation in multiple sports can enhance motor skill development and reduce the risk of injuries.